“WE-PRACTICES WILL HELP BUILDING OUR NNETs IDENTITIES”: STUDENT TEACHERS’ WE-AWARENESS - Saha, Mili (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
The research explores Bangladeshi student teachers’ perceptions about World Englishes (WE) and integrating them into the instructional process. It analyses the teacher learners’ attitudes towards the standard and local varieties of English as a learning goal. Data were obtained from 148 teacher learners pursuing masters in applied linguistics & ELT at a public university. A survey consisting of two demographic and four Likert scale items were used to collect quantitative data on the participants’ WE-awareness. Six respondents participated in the online semi-structured interviews to inform about their perceived values and roles of World Englishes in EFL pedagogies. Results show the student teachers are unaware of WE and its increasing acceptance worldwide. Many participants hold exonormativity about the traditional British varieties despite supporting the integration of local English types in the classrooms. However, having attended a WE-awareness session before interviews, the respondents acknowledge about an impractical and invisible colonial impact on teachers’ mindsets. WE-awareness can promote the use and acceptance of local varieties by constructing the non-native English teachers (NNETs) and ELLs’ identities. Effects of gender and curricula on these perceptions have also been observed. The research calls for integrating WE-awareness into the university teacher preparation curricula to decolonize those.